Controlled generalized fusion frame in the tensor product of Hilbert spaces - Ghosh, Prasenjit; Samanta, Tapas Kumar (Armenian Journal of Mathematics, 2021)
We present controlled by operators generalized fusion frame in the tensor product of Hilbert spaces and discuss some of its properties. We also describe the frame operator for a pair of controlled $g$-fusion Bessel sequences in the tensor product of Hilbert spaces.